IMPACT OF THE PRODUCT QUALITY ON THE SELECTION OF BEEF MARKET USING MULTICRITERIAL ANALYSIS - REIS, João G. M. REIS G. M.; NÄÄS, Irenilza A.; COSTA NETO, Pedro L.O.; VENDRAMETTO, Oduvaldo (Revista Brasileira de Engenharia de Biossistemas, 2010)
The beef market is of great importance to Brazil, and it represents 40% of the agricultural Gross National Product (GNP). Producers try to meet the two types of market, the internal and the export; although just few producers may be adequate to the international norms demands. The internal market consists primarily of raw product in specific cuts which can be purchased in the retail market; while the export market present demands of special requisites, which are range health issues to those involving ethics in production. This research proposes a selection of the beef market by the producer, considering the international standard and using multicriterial analysis advised by the use of the Analytical Hierarchy Process (AHP), besides determining the impact of the application of quality concept within these markets. A main objective (level 1) and three levels of criteria (levels 2, 3 and 4) were selected. Data were processed using the software web based AHPProject®. Results indicated that, although the scenario to meet the requisite for the export market is more complex, this specific market presents more opportunities than the internal market, where the quality is the most important performance criteria to meet the demand of this market.